تحوّلات تعليم المفردات العربية في معهد التبيان: تحليل الانتقال من التجميع الفردي إلى التنظيم المنهجي عبر كتاب نجوى الثريا - Lubis, Mhd Firdaus; Mohammed Abdulaziz Mohammed AhmedEltigani; Hajer Abdallah Albshkar (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
This study aims to analyze the transformations in teaching Arabic vocabulary at Ma’had Al-Tibyan Al-Islami in response to a practical instructional problem, namely the reliance on a traditional method based on individually compiled vocabulary without systematic organization or contextual integration, which led to students’ low comprehension and difficulty in using vocabulary in actual language practice; therefore, a shift was made toward adopting the Najwa al-Thurayya textbook as a structured and graded instructional reference. This research employs a qualitative case study approach to examine transformations across five main dimensions: the source and organization of vocabulary, methods of presentation, the number of daily vocabulary items, the assessment system, and the supervisor’s role in the learning process. Data were collected through document analysis, interviews, observations, and students’ learning experiences. The findings indicate that this transformation improves learning effectiveness by organizing vocabulary progressively, promoting interactive learning, and implementing a systematic assessment system, which in turn increases student participation, enhances their ability to use vocabulary in communicative contexts, and develops overall language competence. The study concludes that shifting from a traditional approach to systematic organization contributes to building a structured mental lexicon and supports sustainable learning, particularly in teaching Arabic to non-native speakers.